Financial Plan of Red Snapper (Lutjanus Sangujnesus) Fishing and Freezing Business In Probolinggo Regency - Mimit Primyastanto (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2018)
The aims of this research is to know the decent of catching and frozen fish company like technical aspect, financial aspect, market aspect, management aspect, effect for the society in Probolinggo, and make a business plan for the frozen fish company. The research method use in this research is deskriptive method, and to collect data used survey method. While for the sample collecting used purposive sample. The kinds of data collected involves primary and secondary data, while for the data analysis used descriptive quantitative and descriptive qualitative analysis. Kakap merah is catching with rawai dasar (bottom long line). In frozen company fish have some process like taking the fish, filleting, triming, cutting, glassing, packaging, freezing, and holding. Profit gained for kakap merah catching in 1 years is Rp 84.012.750,-; Rentabilitas 51,9%; NPV Rp 357.143.082,-; Net B/C 8,45; IRR 191,6%; and Payback Period 4,3 years. While profit gained for frozen fish sector in 1 years have Rp 32.366.767.655,-; Rentabilitas 188%; NPV Rp 146.750.029.164,-; Net B/C 38,4; IRR 835,4%; and Payback Period 3,8 years. Both businesses can be declared feasible and profitable. This sector have average opportunity market 702.293,8 ton/years. For the business planning with 40 catching unit we can produced 825.000 kg/ years. And this sector can take 280 workers, have profit gained Rp 3.192.484.500,-; also can give the poor family with zakat Rp 168.025.500,- every years. While for frozen fish sector we can take 178 workers, have profit gained Rp 30.748.429.272,-; and can give the poor family with zakat Rp 1.618.338.383,- every years.